ENHANCING ELEVENTH-GRADE STUDENTS' VOCABULARY MASTERY THROUGH CROSSWORD PUZZLE: A PEDAGOGICAL INNOVATION AT MA MIFTAHUL QULUB, POLAGAN GALIS PAMEKASAN - Ina Daril Hanna, Ina Daril Hanna; Rini Listyowati, Rini Listyowati; Jaftiyatur Rohaniyah, Jaftiyatur Rohaniyah (Universitas Islam Lamongan, 2024)
This research aims to explore pedagogical innovation by implementing crossword puzzle to enhance students’vocabulary mastery of XI IPA students at MA Miftahul Qulub, Polagan Galis Pamekasan. From the problems that has been found on the observation before, like: Monotonous Teaching Method, Limited Practice Opportunities, Difficulty in Retention, Lack of Active Learning, and Ineffective Assessment in teaching vocabulary so the Classroom Action Research could be the solution. The steps of CAR: Reconnaissance, Planning, Action and Observation, and Reflection. The result of research found that the mean score in pre-test =61.42 cycle 1= 62.14, cycle 2=91.78. There were 28, 6% students passed KKM on pre-test, on cycle 1 just 42, 8% students and 100% students passed the KKM on cycle 2. It proved that the implementation of crossword puzzle can enhance the students’ vocabulary mastery of XI IPA class at MA Miftahul Qulub Polagan Galis Pamekasan